(untitled) (Research, Society and Development, 2022)
It is consensus that Class III treatment is clinically challenging considering, mainly, bone growth. Its diagnosis requires correct assessment of maxillary and mandible involvement since treatment must be directed to the bone base responsible for the malocclusion in order to correct it and provide improvement in the facial pattern. One of the main academic gaps in this subject is the approach to its treatment. In this context, this study aimed to group randomized clinical trials (RCTs) on cephalometric changes observed after maxillary expansion in these dental-skeletal disharmonies. RCTs published in English whose subjects were children and adolescents with Angle class III malocclusion and maxillary atresia were collected. In addition, at least one of the randomized groups should have maxillary (palatal) expansion and the measurement of cephalometric changes observed after palatal expansion as intervention. After inserting the PICO strategy and performing the systematic search, a total of 708 results were retrieved, of which 416 came from Scopus, PubMed, Cochrane, and Web of Science databases. When analyzing cephalometric results, mainly associated with the use of face mask, and considering the limiting factors of this review, it is clear that this type of intervention has become a viable option in clinical practice; however, new qualitative and meta-analytical reviews should be carried out in view of the publication of new randomized clinical trials in order to infer more accurate results and with greater power of evidence.